Gerakan Zero Waste Melalui Penyehatan Pantai, Pembangunan Greenhouse Ecobrick, dan Pelestarian Ekosistem Laut dalam Upaya Mewujudkan SDGs 2030 - Jayanti Dian Eka Sari; Syifa'ul Lailiyah; Diansanto Prayoga; Izzato Millati; Ayik Mirayanti Mandagi; Faisal Fikri; Ratih Novita Praja; Diana Agustina; Siti Nur Hilmin; Yunika Tri Yulianti (Media Gizi Kesmas, 2023)
Background: Banyuwangi Regency is one of the regions in Indonesia which is rich in beach tourism potential, one of which is Pulau Santen Beach which is located in Karangrejo Village, Banyuwangi District, Banyuwangi Regency. However, when the charm of this destination has decreased, the condition of the beach is dirty if left unchecked and no coastal vegetation is carried out, it can damage the marine biota in the vicinity. There is a need for a Santen Island community empowerment program that reviews conservation and sustainable use in order to meet the 14th Sustainable Development Goals (SDGs). Objectives: Community Service entitled "Zero Waste Movement through Beach Environment Sanitation, Greenhouse Ecobrick Development, and Marine Ecosystem Preservation" aims to increase the knowledge, skills and economic independence of the Santen Island community regarding hiding santigi plants, MSME marketing strategies in tourist attractions, and waste management through making ecobricks. Methods: The method used for the implementation of community service is through several stages including, the first stage in this community service program is the preparatory stage. This preparatory stage consists of three steps, namely an environmental survey, purchasing the right sources, and planning a community service program. The second stage of this community service program is the implementation stage and the third advanced stage of this community service program is evaluation. Results: On the first day, there was an increase in the knowledge of the Santen Island community by 18.8%. On the second day there was an increase in public knowledge of 2.2%, and on the third day with ecobrick material there was an increase in public knowledge of 20.2%. This shows that the material can be well captured by the target of community service activities. Conclusions: This activity is later expected to be a provision for the community to revive the tourism potential on Santen Island, namely edutourism which includes aspects of knowledge about cultivating santigi plants, healthy coastal environments through processing inorganic waste into goods of high economic value (ecobricks) and community economic independence through increasing financial capacity new tourism products for edutourism on Santen Island.